2008
DOI: 10.1200/jco.2007.14.6647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Late Treatment-Related Toxicity on Quality of Life Among Patients With Head and Neck Cancer Treated With Radiotherapy

Abstract: Late radiation-induced toxicity, particularly RTOG(swallowing) and RTOG(xerostomia), has a significant impact on the more general dimensions of HRQoL. These findings suggest that the development of new radiation-induced delivery techniques should not only focus on reduction of the dose to the salivary glands, but also on anatomic structures that are involved in swallowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
438
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(455 citation statements)
references
References 21 publications
8
438
2
7
Order By: Relevance
“…While the multivariable regression analysis suggests that those who have more than 5 years diagnosis have lower risk of unmet psychological needs, psychological unmet needs comprise seven out of the ten top needs in this sample and thus remain a priority area to be addressed. If survivors are not supported to regain as much function as possible, or to deal with the physical and psychological challenges they face, this can result in reduced social interactions and reduced psychosocial wellbeing [27], [28].…”
Section: Discussionmentioning
confidence: 99%
“…While the multivariable regression analysis suggests that those who have more than 5 years diagnosis have lower risk of unmet psychological needs, psychological unmet needs comprise seven out of the ten top needs in this sample and thus remain a priority area to be addressed. If survivors are not supported to regain as much function as possible, or to deal with the physical and psychological challenges they face, this can result in reduced social interactions and reduced psychosocial wellbeing [27], [28].…”
Section: Discussionmentioning
confidence: 99%
“…Following conventional, hypofractionated, and combined modality radiotherapy treatments for HNC, studies have shown that long-term treatment related side effects impact on swallowing and nutrition affect QoL and cause distress up to a decade post-treatment (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The radiotherapy treatment for head and neck cancer can be frequently complicated by swallowing dysfunction, xerostomia, dysphonia, and soft tissue fibrosis, affecting the general dimension of quality of life [1][2][3]. To improve tumour local control with lower toxicities, a detailed accuracy in delineating target volumes and OARs is required.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy treatment on head and neck regions is frequently complicated by late effects as swallowing dysfunction, dysphagia, and dysphonia [1,2]. The larynx is involved in complex mechanisms related to swallowing, respiration, and phonation and its irradiation can develop treatmentrelated sequelae [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%